1980
DOI: 10.1002/eji.1830100810
|View full text |Cite
|
Sign up to set email alerts
|

Histamine‐binding suppressor T cells in rabbit peripheral blood

Abstract: Peripheral blood leukocytes (PBL) from primed rabbits were able to suppress the in vitro anti-sheep red blood cell (SRBC) plaque-forming cell (PFC) response of autologous spleen cells. A population containing the suppressor cells could be isolated from PBL by cell fractionation on columns of insolubilized histamine. In contrast to spleen cells, PBL generatd a weak secondary anti-SRBC response in vitro. A strong response was obtained with PBL freed from histamine-binding (H+) cells. The addition of these H+ cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The presence of histamine receptors on mononuclear cells in peripheral blood, and the suppressive role of these cells in inflammation, were confirmed in animal models. Further studies showed that histamine-binding peripheral blood T lymphocytes are responsible for inhibition of inflammation [5]. In 1992, Shibata et al .…”
Section: Histamine As Immunomodulator Of Lymphocyte Activitymentioning
confidence: 99%
“…The presence of histamine receptors on mononuclear cells in peripheral blood, and the suppressive role of these cells in inflammation, were confirmed in animal models. Further studies showed that histamine-binding peripheral blood T lymphocytes are responsible for inhibition of inflammation [5]. In 1992, Shibata et al .…”
Section: Histamine As Immunomodulator Of Lymphocyte Activitymentioning
confidence: 99%
“…As reported previously, a good secondary antibody response can be obtained with such PBL on condition that histamine-binding suppressor T cells are removed [Z]. The cell fractionation procedure on insolubilized histamine and the culture conditions for PBL have been described [25]. The numbers of direct and indirect plaques were determined following the Cunningham method.…”
Section: Induction Of An In Vitro Plaque-forming Cell (Pfc) Responsementioning
confidence: 99%
“…Although the mechanisms responsible for autoimmunity are still poorly defined, both functional and numerical defects in the cells actively suppressing autoaggressive lymphocytes are likely candidates (6)(7)(8). A subset of T cells with the potential to suppress B cells, has been recognized by its ability specifically to bind histamine to membrane receptors (H + T cells) (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Accepted For Publication 21 January I984mentioning
confidence: 99%